Portrayal of Pakistan’s Foreign Policy Towards Yemeni Crisis in Mainstream National Media: A Comparative Analysis of the Daily Dawn and The News - Javid Ahmed Khattak (ASIAN Journal of International Peace & Security (AJIPS), 2021)
This paper aims to examine Pakistan’s foreign policy through the prism of its mainstream national media in a new paradigm shift regarding Yemeni crisis which has shattered peace and security in the Middle East. Conflict in Yemen has also affected the foreign policy of Pakistan which emphasizes a diplomatic solution to this crisis. By and large, Pakistan avoids being viewed as a direct party in the war against Houthi rebels in Yemen, despite Saudi Arabia’s pressure to avert any potential and large-scale sectarian uprising and yet another weave of militancy. Diplomatic efforts are underway for a peaceful resolution of this turmoil. Pakistani media has given extensive coverage to the Yemeni crisis. This paper aims to study the nature of reporting in the national dailies of Pakistan on Yemen’s situation. Editorial pages of Daily Dawn and The News were selected to examine various variables i.e. frequency, frame, slant, and placement of the editorials for 35 days starting from 27- 03-2015 to 30-04-2015 through Content analysis. This study unveils the nature of treatment and depiction of trends and policy in editorials of selected newspapers to project the image of Yemen in this crisis in the light of Framing Theory.